The whole is more than the sum of its parts: addressing insight problem solving concurrently from a cognitive and an affective perspective$deditorial - Danek, Amory H.; Kızılırmak, Jasmin Manuela (Journal of cognitive psychology, 2021)
The last 15 years have witnessed a surge of new studies and increased efforts to better understand the elusive phenomenon of insight. This special issue reflects the expanding field of research on insight problem solving. To counter unresolved definitional and methodological challenges, a series of papers was collected that allows for a high degree of comparability by using similar methods of measurement, including either an assessment of the subjective Aha! experience or restructuring or both. As a result, some converging findings across studies and paradigms could be identified. We believe that future work should continue on this path, moving towards a consensus of how insight should be measured.
Gesehen am 19.01.2022